Comparison of IgA, IgG, and Neutralizing Antibody Responses Following Immunization With Moderna, BioNTech, AstraZeneca, Sputnik-V, Johnson and Johnson, and Sinopharm’s COVID-19 Vaccines - Adjobimey, Tomabu; Meyer, Julia; Sollberg, Leander; Bawolt, Michael; Berens, Christina; Kovačević, Peđa; Trudić, Anika; Parcina, Marijo; Hoerauf, Achim (Frontiers in Immunology, 2022)
In an ongoing multinational trial, we obtained blood samples from 365 volunteers, vaccinated with mRNA vaccines (Moderna, BioNTech), viral DNA-vectored vaccines (AstraZeneca, Sputnik-V, and Johnson and Johnson), or the attenuated virus vaccine from Sinopharm. After collecting reactogenicity data, the expression of S-Protein binding IgG and IgA was analyzed using an automated sandwich ELISA system. Serum neutralizing potentials were then investigated using an ACE-2-RBD neutralizing assay. Moderna’s vaccine induced the highest amounts of SARS-CoV-2 specific antibodies, and serum neutralization activity compared to the other groups. In contrast, Sinopharm and Johnson and Johnson’s vaccinees presented the lowest SARS-CoV-2-specific antibody titers. Interestingly, moderate to high negative correlations between age and virus-specific IgG expression were observed in the Johnson and Johnson (ρ =-0.3936) and Sinopharm (ρ =-0.6977) groups according to Spearman's rank correlation analysis. A negative correlation was seen between age and IgA expression in the Sputnik-V group (ρ =-0.3917). The analysis of virus neutralization potentials in age categories demonstrated that no significant neutralization potential was observed in older vaccinees (61and 80 years old) in the Sputnik-V Johnson and Johnson and Sinopharm vaccinees’ groups. In contrast, neutralization potentials in sera of Moderna, BioNTech, and AstraZeneca vaccinees were statistically comparable in all age categories. Furthermore, while the AstraZeneca vaccine alone induced moderate IgG and IgA expression, the combination with Moderna or BioNTech mRNA vaccines induced significantly higher antibody levels than a double dose of AstraZeneca and similar IgG expression and neutralization potential compared to Moderna or BioNTech vaccines used alone. These results suggest that mRNA vaccines are the most immunogenic after two doses. DNA vectored vaccines from AstraZeneca and Sputnik-V presented lower but significant antibody expression and virus neutralizing properties after two doses. The lowest antibody and neutralization potential were observed in the Sinopharm or Johnson and Johnson vaccinees. Especially elderly over 60 presented no significant increase in neutralizing antibodies after vaccination. The data also indicate that heterologous vaccination strategies combining the AstraZeneca DNA vectored vaccines and mRNA vaccines are more effective in the induction of neutralizing antibodies compared to their homologous counterparts.